Analysis Influence Characteristics CEO to Manipulation Financial Reports on Private Banks in Indonesia - Fauzan Kholish Rabbani; Elly Suryani (LP2M IAIN Palopo, 2025)
This study aims to determine the influence of Chief Executive Officer (CEO) characteristics on indications of financial statement manipulation in the private banking sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. CEO characteristics are measured by three indicators, namely age, gender, and education level, using the F-Score method. The sampling technique used in this study was purposive sampling with a sample of 15 private banks or 75 data on private banking companies listed on the Indonesia Stock Exchange for the 2019–2023 period. The data used are secondary data obtained from the company's annual report and the official IDX website. This research method uses a quantitative method and its analysis uses logistic regression analysis with the help of IBM SPSS 26. The results of the study indicate that CEO characteristics simultaneously significantly influence indications of financial statement manipulation in private banking, supported by control variables such as company size and leverage. However, partially, CEO age, gender, and education level do not significantly influence indications of financial statement manipulation. These findings suggest that CEO characteristics collectively play a role in preventing or encouraging financial statement manipulation in the private banking sector.